Evaluating anticancer properties of Withaferin A—a potent phytochemical - Atteeq, Maushma (Frontiers in Pharmacology, 2022)
Withaferin A is a C28 steroidal lactone derived from the plant Withania somnifera, commonly known as Ashwagandha. Withaferin A has received great attention for its anticancer properties noted in cancer cells of various origins. Extracts of Withania somnifera have been used in traditional Ayurvedic and Unani Indian medicine for their various pharmacological benefits. In recent years, Withania somnifera or Ashwagandha extract has become popularized as a health supplement marketed for its stress and anxiety reducing effects. Withaferin A is one of the most studied withanolides extracted from Withania somnifera that has gained great attention for its anticancer, anti-inflammatory, metabolic, and pro-apoptotic effects. Extensive in vivo and in vitro studies have depicted Withaferin A’s interactions with key role players in cancerous activity of the cell to exert its pro-apoptotic effects. Withaferin A interactions with NF-B, STAT, Hsp90, ER-, p53, and TGF-β have noted inhibition in cancer cell proliferation and cell cycle arrest in G2/M stage, ultimately leading to apoptosis or cell death. This review highlights pro-apoptotic properties of Withaferin A including generation of reactive oxidative species, Par-4 activation, endoplasmic reticulum stress (ER) induction, and p53 activation. Analysis of Withaferin A’s involvement in various oncogenic pathways leading to malignant neoplasm and its pharmacologic activity in conjunction with various cancer drugs provides promising evidence in therapeutic potential of Withaferin A as a cancer treatment.